EFEKTIVITAS PENGGUNAAN DIGITAL STORY POCKETBOOK DALAM MENINGKATKAN PENGETAHUAN REMAJA TENTANG KEGAWATDARURATAN DI SMK YASBU AL-QOMARIYAH SODONGHILIR KABUPATEN TASIKMALAYA - Triya Yestika Shaleha; Yanti Cahyati (Jurnal Kesehatan Mahardika, 2022)
An emergency is a life-threatening situation requiring immediate action to avoid disability and even the victim's death. In dealing with accident cases with emergency conditions, business skills are needed to restore and maintain vital organ functions in accident victims or commonly called Basic Life Support (BLS). The literature review is intended to determine the effectiveness of using Digital Story Pocketbooks (DSP) in increasing adolescent knowledge about emergencies at Yasbu Al-Qomariyah Vocational School Sodonghilir, Tasikmalaya Regency. The method used is the descriptive method. Results: the results obtained before being given DSP had perfect criteria of 12.82% and there was an increase in knowledge with perfect criteria to 71.79% after being given DSP. This DSP can help increase knowledge about the emergency of traffic accidents as a medium of education for students which in the future is expected to improve health status in Indonesia and the response can be faster and more precise to minimize the number of accident victims that cause death.